2023
DOI: 10.3389/fcell.2023.1297292
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targeting of p90 ribosomal S6 kinase

Eric B. Wright,
Deborah A. Lannigan

Abstract: The Serine/Threonine protein kinase family, p90 ribosomal S6 kinases (RSK) are downstream effectors of extracellular signal regulated kinase 1/2 (ERK1/2) and are activated in response to tyrosine kinase receptor or G-protein coupled receptor signaling. RSK contains two distinct kinase domains, an N-terminal kinase (NTKD) and a C-terminal kinase (CTKD). The sole function of the CTKD is to aid in the activation of the NTKD, which is responsible for substrate phosphorylation. RSK regulates various homeostatic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 132 publications
(167 reference statements)
0
2
0
Order By: Relevance
“…To first examine the association between RSK expression and inflammation in human melanoma, we performed correlation analyses using the Skin Cutaneous Melanoma (SKCM) RNA-Seq data set of human melanoma tumors from TCGA PanCancer Atlas. We also included the analysis of transcripts encoding for putative off-targets of BI-D1870, a notorious non-selective RSK inhibitor (reviewed in 18 ). These analyses revealed that all RSK family members correlate positively with inflammation-associated transcripts ( Figure 1A ), while several BI-D1870 targets, such as PLK1, CDK2, and PTK2, showed a 4 negative correlation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To first examine the association between RSK expression and inflammation in human melanoma, we performed correlation analyses using the Skin Cutaneous Melanoma (SKCM) RNA-Seq data set of human melanoma tumors from TCGA PanCancer Atlas. We also included the analysis of transcripts encoding for putative off-targets of BI-D1870, a notorious non-selective RSK inhibitor (reviewed in 18 ). These analyses revealed that all RSK family members correlate positively with inflammation-associated transcripts ( Figure 1A ), while several BI-D1870 targets, such as PLK1, CDK2, and PTK2, showed a 4 negative correlation.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the importance of these findings and the identification of new drug candidates, it is crucial to consider the selectivity of RSK inhibitors since some off-target effects may contribute to the observed anti-tumoral activity. One notorious unselective RSK inhibitor is BI-1870, which was shown to bind the active site of dozens of unrelated kinases such as Polo-like kinase (PLK) 1/3, aurora kinase B, PIK3, and exert RSK-independent effects ( 1316 and reviewed in 17,18 ). For other promising compounds with good biodistribution, tolerability and specific anti-tumoral activities, data on selectivity is often incomplete or unpublished, which may be detrimental to the identification of molecular targets and understanding the mechanism of drug action.…”
Section: Introductionmentioning
confidence: 99%